Training Evaluation For Sme: A Case Of Logam Timur Business Group In Cepogo Timur, Boyolali - Pramudhita, Nurul Bekti; , Dr. Anton Agus Setyawan, SE. M.Si (2016)
Cepogo County has been known as a village that has a lot of copper artisans. However, the businesses is still not well-develop yet. Problems faced by artisans are lack of knowledge of business management, lack of information access to consumers. To increase their knowledge of business management and to access internet information, they were asked to join a training session. Training was conducted in management laboratory, Muhammadiyah University of Surakarta. This study aims to describe of training program for SME, to analyse the evaluation of the training program that was conducted in Muhammadiyah University of Surakarta, and to identify training's need for SME. There are 17 artisans who attended the training; all of them have joined in Logam Timur business group in Cepogo County. Training method used in class training and divided into two section; cost of goods sold and internet marketing. Each section of the training program was hel for two hours. Primary data were collected by distributed the questionnaires after the training session done. There were two types of questionnaires involved, the first one is closed ended-questionnaire which used Likert scale and the second is open ended-questionnaire. The first type of the-questionnaire aims to evaluate the overall effectiveness of the training and open ended-questionnaire aims to get deeper information on what they need in the future while running their business and what kind of material that they need in the next training. This descriptive research will present an evaluation of the training based on the analysis of the questionnaires were collected in table and pie-chart. The result of this study is displayed in four aspects. They are the evaluation of the implementation of the training evaluation, materials evaluation, supporting training evaluation, and the trainers. The training was conducted effectively for all of the aspects. The result score for general aspect is 3,93. Material evaluation aspect's score is 3,98. The aspect of training support is 4,00. For the quality of trainer of cost of goods sold is 3,97 and for trainer of internet marketing is 3,88. To run their business, the participants need investment to increase their business and more training to enhance their knowledge. For the next training, the trainees need material of financial and marketing (41,18 percent of trainees). At the end of this article, there are some identification of needs and wants of metal craftsman to drive their business. A suggestion for Cepogo County and a brief general condition of metal craftsman also are presented in the conclusion part of this article.